Evaluation of deep-frozen ram semen from different sheep breeds with live/dead acrosome staining - Oláh, János (Acta Agraria Debreceniensis, 2007)
It was found that the Kovács – Foote staining is properly adopted to examine deep-frozen ram’s semen. Data are appropriate for comparison. Examination of one ram’s semen per breed is not enough for drawing any conclusions; therefore, I will continue this research.